Integration of Trade and Disintegration of Production in the Global Economy - Robert Feenstra (University of California, Department of Economics, 1998)
The last few decades have seen a spectacular integration of the global economy through trade. The rising integration of world markets has brought with it a disintegration of the production process, however, as manufacturing or services activities done abroad are combined with those performed at home. I compare several different measures of foreign outsourcing, and argue that they have all increased since the 1970s. I also consider the implications of globalization for employment and wages of low-skilled workers, and for trade and regulatory policy, such as labor standards.
Keywords: 330